Analisis Independensi Pemeriksa di Lingkungan Inspektorat Kabupaten Aceh Singkil - Meiniara, Poppy Amalia; Kusmanto, Heri; Isnaini, Isnaini (Universitas Medan Area, 2019)
The aim of this research is to know the effect of personal disturbance, external disturbance and organization disturbance on the auditor’s independence in Inspectorate Aceh Singkil district. The research of variable in this research are personal disturbance, external disturbance, and organization disturbance. The data was collect by the interview to auditor in Inspectorate Aceh Singkil District and the persons in Dinas Lingkungan Hidup Aceh Singkil District. The research proves that personal disturbance, external disturbance, and organization disturbance give effect on the auditor’s independence in Inspectorate Aceh Singkil district.